A historical perspective on the prevalence, distribution and influence of African Horse Sickness in Namibia - Danica Liebenberg; Pieter Warnich; Stuart Piketh; Huib van Hamburg (Contree)
African Horse Sickness (AHS) is a devastating, non-contagious, infectious, insect-borne disease of equids. AHS is endemic to sub-Saharan Africa. Culicoides midges (Diptera: Ceratopogonidae) act as vectors for the transmission of the causative agent, African Horse Sickness virus (AHSV). It is considered to be one of the most lethal horse diseases with mortality rates exceeding 80% in susceptible hosts. The AHS season is one of the most critical times for any horse owner in southern Africa. This dreadful disease has caused losses of great economic and emotional value for as long as horses have been on the African continent. The objective of this article is to assess the historical prevalence, distribution and influence of AHS in Namibia over the past approximately 200 years by discussing historical events that influenced the distribution of this disease. It was found that several major historical events played a role, since the introduction of horses to southern Africa with AHS influenced the outcomes of some of these events. The most important observations made during this investigation were the underreporting of AHS in Namibia, as well as the distribution across the districts. The importance of the effects of AHS on historical events is highlighted, with the limited movement of horses during the AHS seasons being an imperative historical precaution.